Simultaneous scavenging of persistent pharmaceuticals with different charges by activated carbon fiber from aqueous environments. (May 2020) - Zhao, Yufeng; Cho, Chul-Woong; Wang, Dongfang; Choi, Jong-Won; Lin, Shuo; Yun, Yeoung-Sang
Abstract: The adsorptive removal possibility of persistent pharmaceuticals with different charges by activated carbon fiber (ACF) was examined. The pharmaceuticals tested included carbamazepine (CBZ), propranolol (PRO), and diclofenac (DCF), in neutral, cationic, and anionic forms, respectively, which were frequently detected in sewage. The adsorption characteristics of ACF were identified according to the kinetics, isotherm, pH, and ionic strength experiments. The results revealed that ACF can effectively remove these pharmaceuticals, and the adsorption capacities of CBZ, PRO, and DCF by ACF were 1.27 ± 0.06, 1.07 ± 0.08, and 0.95 ± 0.08 mmol g −1, respectively. Moreover, the adsorption of ACF for CBZ was independent of pH and ionic strength, whereas that of anionic diclofenac decreased at alkaline pHs and high concentrations of NaCl. Using a syringe system packed with ACF mat, the scavenging ability of intermittently generated secondary sewage was evaluated. As a result, the residual concentration of PRO and CBZ could not be even detected after consecutive 10 runs in secondary sewage mixture solution. This indicates ACF has the powerful potential for removing pharmaceutical micropollutants in the actual aqueous solutions. FTIR and XPS analyses showed that hydrophobic and π-π interactions and hydrogen bonding contributed to the adsorption process. Graphical abstract: Image 1 Highlights: ACF can effectively scavenge ionic and non-ionic pharmaceuticals from sewage. An ACF mat-equipped syringe system can be used to remove pharmaceuticals simultaneously. ACF syringe system has good durability and system robustness. Hydrophobic, π-π interactions, and H-bonding contribute to the adsorption process.